Introducing the Apocrypha : Message, context, and significance, David A. DeSilva : book review - Branch, Robin Gallaher (Old Testament essays, 2003)
Extracted from text ... 788 BOOK REVIEWS , 784-800 DeSilva, David A 2002. Introducing the Apocrypha: Message, context, and significance. Grand Rapids, MI: Baker Academic. 428 pages. Cloth with dust cover. US $29, 99. ISBN 0-8010-2319-X. David A deSilva, Professor of Greek and New Testament at Ashland Theological Seminary in Ohio, has written a valuable overview of the Apocrypha that is certain to become a standard text. The Apocrypha, defined as works not contained in the canon of the Hebrew Bible (p 10), is a body of literature that has fascinated readers of the biblical text for millennia. DeSilva maintains the Apocrypha is ..